Maine’s Three Ring Binder - Kittredge, Fletcher (Maine Policy Review, 2013)
Although Maine is a rural state, it has had success in keeping pace with technological changes since the rise of the Internet 20 years ago. In this section, authors describe some of these successes and the challenges faced by both consumers and libraries in the new digital environment. Fletcher Kittredge presents the history and promise of Maine’s “Three Ring Binder,” a new and important fiber optic network that will bring high-speed broadband connectivity to rural parts of the state. The Three Ring Binder is expected both to improve economic opportunities for businesses and to increase high-speed Internet access for underserved populations.
Keywords: Internet; telecommunications; fiber optic cable; broadband